Efeitos da suplementação com Beta-Hidroxi-Beta-Metilbutirato (HMB) sobre o tecido ósseo de ratos submetidos ao tratamento com dexametasona em curto prazo - Andreo, Camile Bermejo (2015)
Currently, glucocorticoids are widely used in human medicine for the treatment of several chronic diseases, such as inflammatory and autoimmune diseases. In the UK, some 250,000 people (10% are children), undergo systemic treatment with corticosteroids owing to various causes. Epidemiological studies have shown that 50% of patients with rheumatoid arthritis are treated with glucocorticoids continuously, however, the use of glucocorticoids, such as dexamethasone, depending on the dosage and time used, has caused undesirable effects on bone and muscle tissues, such as osteopenia and sarcopenia. An alternative to reduce the undesirable effects of dexamethasone is the use of beta-hydroxy-betamethylbutyrate (HMB), because some studies have shown that HMB has beneficial effects on bone and muscle tissues, such as muscle cell hypertrophy, increased muscle strength, increased final weight of the carcasses of production animals and improvement in bone mineral density. Thus, the present study aims at assessing, in an animal model (Rattus norvegicus), whether the use of dexamethasone for a short period (10 days) induces changes in bone tissue, related to bone loss, and if the use of HMB prevents such changes. Thirty-two animals were divided into the following groups: control group treated with saline solution (CG); experimental group treated with dexamethasone (DEG); experimental group treated with HMB (HEG) and experimental group treated with both dexamethasone and HMB (DHEG). All groups were treated for 10 days, once a day, and following euthanasia, the animals had both removed for bone tissue assessment, using histological, birefringence and biomechanical analyses. Histological analyzes were performed descriptively by hematoxylineosin (H&E) staining and the birefringence analysis of the collagenous matrix by the polarization method with Picrosirius Red. Additionally, bone biomechanical parameters, such as maximum load, fracture strength, resilience, toughness and stiffness were analyzed. No significant differences were seen among the groups assessed, neither in the descriptive morphological analysis (H&E), nor in the birefringence pattern analysis of the collagenous matrix (Picrosirius Red). Furthermore, no significant difference was observed among the groups when biomechanical parameters were assessed. Thus, the results showed that shortterm treatments with dexamethasone, HMB, or simultaneously (dexamethasone and HMB) did not induce changes in bone tissue.